Analysis of Agropolitan Area Development in Tinggimoncong Sub-District, Gowa District, South Sulawesi - Rian Alfadillah; Fadillah Putra; Mahir; Luthfia Ayu Dhea (Jurnal Penelitian Pendidikan IPA, 2024)
Assessing the problems of economic growth, urbanization, and development prospects in Tinggimoncong District, Gowa Regency, South Sulawesi, Indonesia, have yet to catch up due to economic growth concentrated in cities. The concept of "Agropolitan" has been proposed to address this problem. The agropolitan concept combines human resources, natural resources, and added value in the agricultural sector to advance rural areas. Tinggimoncong sub-district has great potential to become an agricultural centre in the Gowa District for various types of crops. This study aims to analyze the status of sustainability and build appropriate strategies in the development of a rural area of horticultural agricultural production centres. The analysis method is multidimensional scaling (MDS) and SWOT. The results of this study indicate that agropolitan development strategies in Tinggimoncong District can utilize strong internal strengths, such as improving the quality of agricultural products, establishing an agricultural product processing industry, increasing training, and planning for the effective use of agricultural tools and machinery. In addition, it is also important to pay attention to ecological sustainability by educating farmers about good crop rotation, the use of organic materials as fertilizers, and sustainable soil conservation efforts. Cooperation between the government, farmers and various related parties can be the key to success in implementing the agropolitan concept and ensuring the sustainability of the region.